Psychometric properties of the Marital Satisfaction Scale in workers in southern Peru - Rojas Quispe, Santiago David (2024)
The study addressed the objective of identifying the psychometric properties of the marital satisfaction scale in workers from southern Peru. The study was psychometric in nature, where the psychometric properties of the scale were identified in an organizational context of the Peruvian Altiplano. There was participation of 300 couples who were married and living together. The scale in its originality was validated in a Mexican context, from which it was transferred to apply in the Peruvian context. The results show good goodness-of-fit indices such as Chi Square = 326.331 and degrees of freedom = 149, with a value of χ2/df = 2.190, which indicates a good fit and an acceptable model. In addition, the CFI = 0.938, TLI = 0.929, RMSEA = 0.063, GFI = 0.902 and SRMR = 0.025. In conclusion, the marital satisfaction scale is suitable for future studies.